2015
DOI: 10.1016/j.jand.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Differential Improvements in Student Fruit and Vegetable Selection and Consumption in Response to the New National School Lunch Program Regulations: A Pilot Study

Abstract: Background This study investigated changes in student food selection and consumption in response to the new National School Lunch Program meal patterns during fall, 2011. Design Eight elementary and four intermediate schools in one Houston area school district were matched on free/reduced price (FRP) meal eligibility and randomized into control or intervention conditions. Intervention Both intervention and control school cafeterias served the same menu. The intervention school cafeterias posted the new mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 17 publications
3
56
0
Order By: Relevance
“…Our qualitative findings are consistent with and complement several recent quantitative studies related to school meal reform. Studies have reported that overall, student selection and consumption of fruits and vegetables increased after implementation of the new meal standards . In addition, FSDs' references to the importance of the “bigger puzzle” in children's health are consistent with a body of literature that identifies schools as one component of a complex and dynamic system influencing children's health .…”
Section: Discussionmentioning
confidence: 57%
“…Our qualitative findings are consistent with and complement several recent quantitative studies related to school meal reform. Studies have reported that overall, student selection and consumption of fruits and vegetables increased after implementation of the new meal standards . In addition, FSDs' references to the importance of the “bigger puzzle” in children's health are consistent with a body of literature that identifies schools as one component of a complex and dynamic system influencing children's health .…”
Section: Discussionmentioning
confidence: 57%
“…Related to discussions on the effect of availability of specific food items, a choice between different food options within a food category in contrast to a no‐choice condition has proved to increase the liking and consumption of the respective food category for children. Two intervention studies that either introduced a forced choice (compared to a no‐choice condition) between different F&V (Hakim & Meissen, ) or increased the number of choice options from two to three servings (Cullen, Chen, Dave, & Jensen, ) in school canteens both found increases in the intake of F&V under constant or decreasing shares of leftovers. Rohlfs Domínguez et al () extended these findings by the notion that it did not make a difference whether children had a choice between two vegetables before the beginning of a meal (regular service line) or during their meal (family‐buffet style which allows spontaneous decision making) but that both possibilities of choice increased average vegetable intake compared to a no‐choice condition.…”
Section: Resultsmentioning
confidence: 99%
“…Five trained data collectors 19 visited each school weekly in an assigned rotation during February and March, 2013, so that the observations were conducted on all days of the week in all eight schools. The menu items were preprinted on observation sheets.…”
Section: Methodsmentioning
confidence: 99%